Percutaneous kyphoplasty for the treatment of distal lumbosacral pain caused by osteoporotic thoracolumbar vertebral fracture. (November 2018) - Niu, Junjie; Song, Dawei; Gan, Minfeng; Liu, Bin; Tan, Chenglong; Yang, Huilin; Meng, Bin
Background: Kyphoplasty has been demonstrated to be minimally invasive and effective in treating osteoporotic vertebral fracture patients with back pain over the level of the fractured vertebrae. Rare studies have reported on thoracolumbar vertebral fracture patients presenting with distal lumbosacral pain (DLP). Whether kyphoplasty had a favorable therapeutic benefit for these patients remains unclear. Purpose: To evaluate the therapeutic efficacy of kyphoplasty in treating osteoporotic thoracolumbar vertebral fracture (OTVF) patients with DLP and assess the clinical significance of focal tenderness to palpation in these patients. Material and Methods: Thirty-two OTVF patients who only complained of DLP were treated by kyphoplasty. The vertebral heights, local kyphotic angle, Visual Analogue Scale (VAS), and Oswestry Disability Index (ODI) scores were assessed preoperatively, one day after surgery, and at last follow-up. All patients were evaluated regarding their degree of satisfaction with kyphoplasty. In addition, we compared the therapeutic efficacy of kyphoplasty in patients with and without focal tenderness to palpation. Results: All patients successfully underwent kyphoplasty without complications. The vertebral heights, local kyphotic angles, VAS, and ODI scores were all significantly improved after kyphoplasty and maintained at last follow-up in our patients ( P  < 0.001). At last follow-up, all patients expressed satisfaction with kyphoplasty. No significant differences in these parameters were detected between patients with and without focal tenderness. Conclusion: The possibility of thoracolumbar vertebral fractures in elderly patients complaining of DLP should not be neglected. Kyphoplasty presents a superior benefit in treating OTVF patients with DLP. The absence of focal tenderness does not influence the clinical efficacy in these patients.